Effect of Various Post Harvest Treatments on Storage Behaviour of Aonla cv. Chakaiya - Thokchom, Rocky; Mandal, Goutam (International Journal of Bio-resource and Stress Management, 2018)
The present laboratory investigation was aiming to assess the influence of various post-harvest treatments on storage behaviour of aonla fruits during the year 2015–16 in the ‘Department of Horticulture and Post-Harvest Technology, Institute of Agriculture, Visva-Bharati, Sriniketan’. Freshly harvested physiological mature fruits of aonla cv. Chakaiya of uniform size, shape, colour, free from disease and bruises were given various post-harvest treatment of gibberellic acid (GA3: 50 ppm, 100 ppm), naphthalene acetic acid (NAA: 20 ppm, 30 ppm) and calcium chloride (CaCl2: 1, 1.5%) and were air dried and kept in 5 ply corrugated boxes (5% ventilations) with newspaper lining and stored in room temperature. The fruits were analysed for various quality attributes at different storage intervals up to 12 days. The results revealed that physiological loss in weight (4.94, 7.06 and 9.04%) and spoilage percent (0, 0 and 15%) of the fruits remain minimum after 4, 8 and 12 days respectively in CaCl2 (1%) treated fruits during storage. Whereas, TSS (9.28, 10.82 and 1 2.46 oB), acidity (2.31, 2.08 and 1.89%), ascorbic acid (475.06, 456.70 and 413.13 mg 100 g-1) and total sugar (7.86, 8.20 and 8.62%) of the fruits were highest after 4, 8 and 12 days respectively in GA3 (100 ppm) treated fruits during storage. This study shows that the storability and quality of aonla fruits can be favourably influenced during storage when treated with calcium chloride and GA3.